THE FACTORS INFLUENCING TOURIST VISITATIONS NUMBER IN CURUG SILAWE - Prakosa, Novian Hangga; Fafurida, Fafurida (Universitas Negeri Semarang, 2019)
The purposes of this research are to identify the influence of travel cost, income, distance, access, facilities, natural beautiness, and age on the number of individual visits to Curug Silawe and to estimate the economic value of Curug Silawe through individual travel cost method. The population in this study are tourists that visited Curug Silawe with sample of 98 respondents taken by the quota accidental sampling technique. The data collection method used are literature study and questionnaire. The analysis tool used are OLS linear regression and economic value estimation. The results showed the variables that influence the number of individual visits to Curug Silawe are income, distance and age. Income and age has a positive effect. While distance has a negative effect. The economic value of Curug Silawe reached IDR 1,109,930,140.48 per year. This value is obtained from consumer surplus obtained per individual per year of IDR 308,656.88. Tujuan dari penelitian ini adalah untuk mengidentifikasi pengaruh biaya perjalanan, pendapatan, jarak, akses, fasilitas, keindahan alam, dan usia pada jumlah kunjungan individu ke Curug Silawe dan untuk memperkirakan nilai ekonomi Curug Silawe melalui metode biaya perjalanan individu . Populasi dalam penelitian ini adalah wisatawan yang berkunjung ke Curug Silawe dengan sampel 98 responden yang diambil dengan teknik quota accidental sampling. Metode pengumpulan data yang digunakan adalah studi literatur dan kuesioner. Alat analisis yang digunakan adalah regresi linear OLS dan estimasi nilai ekonomi. Hasil penelitian menunjukkan variabel yang mempengaruhi jumlah kunjungan individu ke Curug Silawe adalah pendapatan, jarak dan usia. Penghasilan dan usia memiliki efek positif. Sedangkan jarak memiliki efek negatif. Nilai ekonomi Curug Silawe mencapai Rp1.109.930.140,48 per tahun. Nilai ini diperoleh dari surplus konsumen yang diperoleh per individu per tahun sebesar Rp308.656,88.